Análise do discurso de sujeitos afásicos em um grupo de convivência - Moura, Maria Martins Amorim de (2011)
Aphasia is characterized by a language change due to a brain injury. The aphasic person presents difficulties in the linguistic process, and may also presents motor, sensory and emotional problems, which, this way, reflect on his or her social environment. The literature that studies aphasia presents an organicist perspective, focusing only on the neurological cause, in which the relationship between neurological order and language order is done directly. Realizing that aphasia should be thought in a more broadly way, not restricted to the disease only, but also to the person who has the disease, is the reason for the French Discourse Analysis line to be used. Thus, the overall objective of this study was to analyze the speech of aphasic people in a linguistic-discursive perspective. Specifically, it is intended to investigate the speech of aphasic people with the diagnosis of brain injury and neurological speech disorder of similarity and contiguity; to describe the aphasic people linguistic and discursive production characteristics; and to identify strategies which generate linguistic-discursive effects shift on the people under study language. The aphasics who participated in this study were part of the Catholic University of Pernambuco (UNICAP) aphasic social group, which aims to work out the issues related to language. Data was collected by recordings, both in audio and video, from the workshops held in the aphasia Group, with varied themes. For data anal sis, speech cuttings ere taken from the aphasics interaction discursive moments in the group. The discursive cutting is a piece of discourse situation that the researcher uses to analyze the people evaluated discursive production. The discursive situations analysis focused here enabled the answers for the suggested questions addressed in this work. Considering the results, it was observed, as an aphasic discursive characteristic, the erasure of the speaker condition done by the person itself. It was also observed that the attitude taken by the Speech Therapist, in some situations, causes silencing on the aphasic. And that some activities generate displacement effect on the speech of these people. These activities were those in which the language was always present, showing its importance in the people therapeutic process. This makes it clear that professionals working with the aphasic person, especially the Speech Therapist, cannot avoid the use of a therapy which would contemplate, in essence, the language functioning